The impact of effective corporate tax rates on investment (2020)
There exists an intense debate about the effects of corporate tax cuts on the formation of private capital in the real sector. This paper studies the investment impact of the effective fiscal burden of firms during the period 1995-2014. To this end, in a first step national accounts data is used to calculate backward looking average Effective Corporate Tax Rates (ECTR) for 73 developed and developing countries. In a second step, a dynamic panel approach is employed to estimate the impact of the ECTR on private gross fixed capital formation and foreign direct investment inflows. The obtained results indicate that: (i) ECTR not only tend to be much lower than statutory corporate tax rates, but also have different dynamics over time; and (ii) there exists no clear statistically significant negative relationship between ECTR and private investment. Instead, private capital formation and FDI inflows are rather explained by economic growth, the persistence of investment spending, trade openness, and the quality of institutions. This finding is robust when alternative effective corporate tax rate measures or statutory corporate tax rates are considered